Integrative taxonomy uncovers two new pontarachnid mite species from the eastern Mediterranean and Red Sea (Pontarachnidae, Hydrachnidia, Acari) - Pešić, Vladimir; Bańkowska, Aleksandra; Rewicz, Tomasz; Górecka, Ewa; Asif, Maryam; Zawal, Andrzej (Zootaxa, 2026)
The diversity of Pontarachnidae, the only family of hydrachnid mites occurring in marine environments, remains poorly documented morphologically and molecularly in the Mediterranean Sea and adjacent marine ecosystems, including the Red Sea. Using an integrative taxonomic approach, we described two new species: Litarachna cypriotica sp. nov. from the eastern Mediterranean (Cyprus) and Pontarachna goldschmidti sp. nov. from the Red Sea (Egypt). Interspecific K2P genetic distances exceeded 17% for both new species. Species boundaries were consistently supported across all applied species delimitation analyses. In addition, the presence of Litarachna smiti Pešić, Chatterjee & Ahmed Abada, 2008 was molecularly confirmed for Egypt for the first time, and Pontarachna punctulum Philippi, 1840 was proposed to be removed from the list of Red Sea pontarachnid mites. This study underscores the largely unexplored diversity of pontarachnid mites and highlights the importance of molecular approaches in elucidating the evolutionary mechanisms underlying this diversity.